Determinants of tuberculosis treatment support costs to the treatment supporters in rural Ghana - Robert Bagngmen Bio; Patricia Akweongo; Augustine Adomah-Afari; Augustina Koduah (AIMS Public Health, 2023)
Background: The Ghana Health Service has been implementing the Directly Observed Therapy Short Course (DOTS) strategy for decades now, to cure and reduce the transmission of tuberculosis. DOTS strategy requires TB patients and their treatment supporters to make multiple clinic visits in the course of treatment, and this may place financial burden on treatment supporters with low socio-economic status. However, the determinants of tuberculosis treatment support costs to treatment supporters are unknown in Ghana.